Electro spun dual structured and three-dimensional biodegradable scaffolds for bone and cartilage tissue engineering - Vidya Chamundeswari Narasimhan (2018)
Tissue engineering (TE) is envisaged to play a vital role in improving the quality of life by restoring, maintaining or enhancing tissue and organ functions. TE scaffolds that are two dimensional (2D) in structure suffer from undesirable issues, such as pore blockage, and do not closely mimic the native extra-cellular matrix (ECM) in tissues. Significant efforts have therefore been channeled to fabricate structurally diverse scaffolds using various techniques, especially electrospinning. Electrospinning is a cost effective, reliable, versatile and scalable technique that has widely been explored for fabrication of tissue engineered scaffolds. The aim of this study is to investigate the efficacy of a dual structured and 3-Dimensional (3D) polymeric scaffold to support and enhance tissue differentiation into desired lineage. The dual structured scaffold contains micro-particles electro sprayed onto a fibrous mesh like network. The entire structure resembles a sandwich in appearance and both the micro-particles and the nanofibers are loaded with different bioactive molecules prior to electrospinning. This study makes use of single electrospinning equipment to electro spray and electro spin the dual structured scaffold. The polymeric scaffold is made from a combination of PLGA/PCL (poly lactide co glyceride/poly capro-lactone) blend in a ratio of 1:1. The scaffold releases up to three different biomolecules simultaneously. The fate of mesenchymal stem cells (MSCs) towards differentiating into osteogenic or chondrogenic lineage has been evaluated using different combinations of bioactive molecules. Further, a modified one-step electrospinning process to arrive at a three-dimensional (3D) scaffold with highly interconnected pores was investigated. Using a blend of hydrophobic and hydrophilic polymers, this mechanically viable, sponge-like 3D scaffold exhibited sufficiently large pores and enabled cell penetration beyond 500 μm. The release study was initially carried out with an anti-inflammatory agent – Dexamethasone (Dex). Dex loaded fibers exhibited a sustained release for up to 30 days depending on the polymer blend used for fabrication. Further, the potential of this Dex-loaded 3D scaffold was evaluated for upregulation of osteogenic genes with MSCs. The as-produced Dex-loaded 3D scaffold possesses a unique intertwined sub-micron fibrous morphology that can be tailored for use in bone tissue engineering and beyond. The efficacy of this 3D scaffold was finally evaluated for sustained release of two hydrophilic biomolecules that have applications in the arenas of bone and cartilage tissue engineering. For directing bone tissue regeneration, the scaffold was loaded with Ascorbic acid (AA) and ß- Glycerophosphate (ß-Gly) and electro spun prior to MSC seeding. For inducing cartilage formation, the biomolecules of interest were AA and Proline (Pro). The scaffolds were seeded with MSCs and cultured for three weeks at the end of which gene upregulation and immunohistochemical studies were conducted. Hence using a single technique, two morphologically different scaffold systems were established for addressing issues of sustained release of multiple bioactive agents, cell penetrability and for directing the fate of MSCs into desired lineage. These scaffold systems (dual structured and 3D) can be tailored to suit different applications for engineering the ECM and reducing the ever-increasing gap between demand and supply of tissue engineered constructs.